2000
DOI: 10.1083/jcb.149.4.969
|View full text |Cite
|
Sign up to set email alerts
|

The Tetraspan Molecule Cd151, a Novel Constituent of Hemidesmosomes, Associates with the Integrin α6β4 and May Regulate the Spatial Organization of Hemidesmosomes

Abstract: CD151 is a cell surface protein that belongs to the tetraspan superfamily. It associates with other tetraspan molecules and certain integrins to form large complexes at the cell surface. CD151 is expressed by a variety of epithelia and mesenchymal cells. We demonstrate here that in human skin CD151 is codistributed with α3β1 and α6β4 at the basolateral surface of basal keratinocytes. Immunoelectron microscopy showed that CD151 is concentrated in hemidesmosomes. By immunoprecipitation from transfected K562 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
211
2
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(228 citation statements)
references
References 78 publications
12
211
2
3
Order By: Relevance
“…They include epithelial cells migrating over injured airway, 5 rat corneal squamous epithelium during wound healing after excimer keratectomy 42 and carcinoma cells in human cancer tissues such as colon adenocarcinomas, 14 infiltrative basal cell carcinomas and squamous cell carcinomas of the skin. 43 CD151 is localized to basal cells of stratified squamous cell epithelium 22,24,44,45 and the basolateral layer of enterocytes on villi. 22 Although information about localization in carcinoma cells is limited, our immunohistochemical and in situ zymographical studies on the human lung adenocarcinoma tissues have demonstrated colocalization of CD151 and MMP-7 on the carcinoma cell membranes and MMP-7 activity at the carcinoma cell nests.…”
Section: Promatrilysin-1 Activation Through Interaction With Cd151 T mentioning
confidence: 99%
See 2 more Smart Citations
“…They include epithelial cells migrating over injured airway, 5 rat corneal squamous epithelium during wound healing after excimer keratectomy 42 and carcinoma cells in human cancer tissues such as colon adenocarcinomas, 14 infiltrative basal cell carcinomas and squamous cell carcinomas of the skin. 43 CD151 is localized to basal cells of stratified squamous cell epithelium 22,24,44,45 and the basolateral layer of enterocytes on villi. 22 Although information about localization in carcinoma cells is limited, our immunohistochemical and in situ zymographical studies on the human lung adenocarcinoma tissues have demonstrated colocalization of CD151 and MMP-7 on the carcinoma cell membranes and MMP-7 activity at the carcinoma cell nests.…”
Section: Promatrilysin-1 Activation Through Interaction With Cd151 T mentioning
confidence: 99%
“…27 All these data support the notion that CD151 is a positive effecter of metastasis. As CD151 is able to bind with various integrin species, especially a3b1 and a6b4 integrins, it has been suggested that CD151-integrin protein complexes may play a role in cell motility probably through modulation of the interaction between integrin and ECM such as laminin-5 24 and also activation of focal adhesion kinase. 46 However, these studies have completely lacked information about proteinases, which are also essential to tumor cell invasion and metastasis.…”
Section: Promatrilysin-1 Activation Through Interaction With Cd151 T mentioning
confidence: 99%
See 1 more Smart Citation
“…Dans la décennie qui suivit, la fonction dans la régu-lation de ces processus cellulaires d'autres tétraspa-nines, en interaction avec les intégrines, a été étudiée. Ainsi, par des expériences d'immunofluorescence, il a été montré que les protéines CD9, CD81 et CD151 sont fortement exprimées dans les kératinocytes en culture α3β1, α6β1 et α4β1 [5][6][7] pour réguler leurs fonctions, comme l'attestent des expériences de mutagenèse dirigée visant à introduire des mutations dans les domaines fonctionnels de CD151 [8][9][10]. Les tétraspanines possèdent une structure commune comprenant quatre régions hydrophobes hautement conservées, transmembranaires, flanquées de courtes séquences intracytoplasmiques N-et C-terminales et de deux boucles extracellulaires de tailles inégales (les domaines EC1 et EC2) (Figure 1).…”
Section: Le Rôle Des Tétraspanines Dans L'homéostasie Cutanée Les Tétunclassified
“…Master Regulator of Laminin-Binding Integrins CD151 forms stable, lateral complexes with laminin-binding integrins, ie, a3b1, a6b1 and a6b4 crucial in cancer cell migration and invasion [36][37][38] (Figure 1). Integrin subunits a3 and a6 directly interact with CD151 through the QRD [194][195][196] site at the extracellular loop of the protein.…”
Section: Cd151 Structure and Functionmentioning
confidence: 99%